Annual Development Plan of Madhya Pradesh 1960-61 - Planning Commission (Planning Commission, 1960)
The new State of Madhya Pradesh comprises the 17 districts of Mahakoshal, the whole of Madhya Bharat (excluding the Sunel enclave), Vindhya Pradesh md Bhopal States and the Sironj sub-division of Kotah district of Rajasthan. It is situated between latitudes of 18°N and 261/2°N and between longitudes 74° E and 841/2°E. The main physical features of the State are Gird region, the Malwa Plateau, the Narmada valley, the Satpura range and the Chhattisgarh plains; The main river systems are the Chambal, the Betwa, the Sone, the Narbada, the Tapti, the Mahanadi and the Indrawati. The annual rainfall in The State varies from 30' to 60' in Mahakoshal region, 30' to 40' in Malwa region, 30' to 35' in Vindhya Pradesh region and 30' to 50' in Bhopal region.
Government of Madhya Pradesh, Planning and Development Department